EAHP European Statements Survey 2017, focusing on sections 2 (Selection, Procurement and Distribution), 5 (Patient Safety and Quality Assurance) and 6 (Education and Research). Issue 5 (31st July 2018) - Horák, Petr; Underhill, Jonathan; Batista, Aida; Amann, Steffen; Gibbons, Nicholas
Abstract : Objectives: The 2017 EAHP European Statements Survey focussed on sections 2, 5 and 6 of the European Statements of Hospital Pharmacy. Statistical data on the level of implementation and on the main barriers to implementation of the Statements were collected. A further aim was to identify barriers in general, such as lack of awareness. Methods: An online questionnaire was sent to all hospital pharmacies in European Association of Hospital Pharmacists (EAHP) member countries. Data were analysed at Keele University School of Pharmacy, UK by and the EAHP Survey Group. Results: There were 783 complete responses (response rate 17.4%). Some 42% of responders worked in teaching hospitals, 76% of hospital pharmacies had 10 or less pharmacists, and 46% of hospital pharmacies served over 500 beds. Five questions revealing the lowest implementation levels were further analysed in greater detail. Only 30% of respondents reported that their hospital pharmacists routinely publish hospital pharmacy practice research, and only 50% are involved in the development of local or national guidelines. 45% of respondents reported that computerised decision support was used to reduce the risk of medication errors in their hospitals, 69% stated that they had contingency plans for medicines shortages and 60% answered that they had had reason to contact their medicines authority because of drug shortages. 63% reported that the transcription step had been eliminated from the medicines administration process. Conclusions: The survey has provided the EAHP with an overview of the implementation level as well as the barriers to and drivers of implementation of sections 2, 5 and 6. This is important for informing the plans of EAHP and its members so that implementation can be fully supported.